Use of Chitosan as Low Cost Source to Overcome Endophytic Contaminations under In vitro Conditions (Plant Tissue Culture and Biotechnology, 2019)
Abstract not availablePlant Tissue Cult. & Biotech. 29(1): 121-126, 2019 (June)